2009
DOI: 10.3342/ceo.2009.2.3.145
|View full text |Cite
|
Sign up to set email alerts
|

Results of Air Caloric and Other Vestibular Tests in Patients with Chronic Otitis Media

Abstract: ObjectivesAir caloric results are supposed to be influenced by anatomic changes of the middle ear. The aims of our study were to evaluate the incidence and characteristics of abnormal air caloric results in patients with unilateral chronic otitis media and without any history of vertigo, and to compare caloric results with there of other vestibular function tests (VFTs).MethodsTwenty five patients with unilateral chronic otitis media (COM) who were scheduled for surgery underwent VFTs preoperatively. Hearing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
4
21
0
Order By: Relevance
“…The association between threshold elevation in extended high‐frequencies (without hearing loss in standard audiometry) and tinnitus has been reported in the past . The correlation between otitis media and tinnitus, to our knowledge, has not been systematically studied in the past; nevertheless, it has been estimated that 18% to 43% of patients with chronic otitis media complain of tinnitus during the evolution of the disease This number may, however, increase up to 79% when considering patients who have associated vestibular symptoms . Park et al, in a study involving eight subjects who showed sensorineural hearing loss in standard audiometry following acute otitis media, found tinnitus in 87.5% of these patients.…”
Section: Discussionmentioning
confidence: 98%
“…The association between threshold elevation in extended high‐frequencies (without hearing loss in standard audiometry) and tinnitus has been reported in the past . The correlation between otitis media and tinnitus, to our knowledge, has not been systematically studied in the past; nevertheless, it has been estimated that 18% to 43% of patients with chronic otitis media complain of tinnitus during the evolution of the disease This number may, however, increase up to 79% when considering patients who have associated vestibular symptoms . Park et al, in a study involving eight subjects who showed sensorineural hearing loss in standard audiometry following acute otitis media, found tinnitus in 87.5% of these patients.…”
Section: Discussionmentioning
confidence: 98%
“…This may be due to gradual vestibular compensation [9]. Rotatory chair abnormalities were reported in 70.1% of the patients, caloric weakness was found in 61.6% and VEMPs were abnormal in 23.3% [9,10,12,13]. Moreover, the relationship between vertigo and SNHL (57.1%) was just close to statistical significance [1,3].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [22] demonstrated that despite any complaint of definite vestibular symptoms, an high incidence of vestibular impairment in patients with unilateral COM was observed.…”
Section: Discussionmentioning
confidence: 99%